2008
DOI: 10.1111/j.1472-4642.2008.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

The potential for hull‐mediated species transfers by obsolete ships on their final voyages

Abstract: Shipping has contributed strongly to biological invasions in coastal ecosystems, transferring species in ballast tanks and on exposed underwater surfaces (hulls). A long history exists that documents biota associated with ships’ hulls, including some recent analyses of modern ships, but relatively little is known about the associated risks of invasion. In general, the likelihood of invasion is expected to increase with increasing propagule supply, which suggests that high‐density transfers on hulls may pose a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 35 publications
3
47
0
1
Order By: Relevance
“…The SCAMP method of in-water scrubbing can be considered favorable to no pre-departure management effort, however, even though we recorded viable specimens from a majority of species on the ORION after scrubbing. Moreover, comparisons between this study and another of two similar vessels (Davidson et al, 2008), suggest that in-water cleaning is more effective at creating bare space and removing organisms than transit alone. Holm et al (2003) have demonstrated that several factors, including brush position, brush angle, rotation rate, bristle density and bristle stiffness, interact in a complex manner to determine the forces required to remove organisms from submerged surfaces.…”
Section: Bio Fo Ul In G An D In -Water Cl Ean In Gmentioning
confidence: 67%
See 3 more Smart Citations
“…The SCAMP method of in-water scrubbing can be considered favorable to no pre-departure management effort, however, even though we recorded viable specimens from a majority of species on the ORION after scrubbing. Moreover, comparisons between this study and another of two similar vessels (Davidson et al, 2008), suggest that in-water cleaning is more effective at creating bare space and removing organisms than transit alone. Holm et al (2003) have demonstrated that several factors, including brush position, brush angle, rotation rate, bristle density and bristle stiffness, interact in a complex manner to determine the forces required to remove organisms from submerged surfaces.…”
Section: Bio Fo Ul In G An D In -Water Cl Ean In Gmentioning
confidence: 67%
“…The high levels of biofouling with little variation among hull locations found on the ORION represent common features of stationary vessels that receive little or no hull husbandry (Brock et al, 1999;DeFelice, 1999;Coutts, 2002;Minchin and Gollasch, 2003;Davidson et al, 2008). Such vessels tend to have extensive biofouling assemblages in both hull and non-hull areas that exceed niche area fouling of most operational ships.…”
Section: Bio Fo Ul In G An D In -Water Cl Ean In Gmentioning
confidence: 98%
See 2 more Smart Citations
“…Alternatively, the service time of vessels may decrease as the capacity to accommodate more transits increases. This decrease could reduce the establishment probability of organisms attached to the hulls of arriving vessels, as residence time and likelihood of invasion are thought to be positively correlated (Davidson et al, 2008).…”
Section: Evaluating Future Changes In Panamamentioning
confidence: 99%